Numerical simulation of acoustic agglomeration of fine particles in sintered flue gas of steel production. Issue 1 (May 2020) - Zhao, Yun; Zhou, Hefeng; Tian, Zhangfu; Zeng, Xinwu; Gong, Changchao
Abstract: Fine particles in the sintering flue gas of steel production account for the vast majority, which is the primary control object of PM2.5 emission sources. Traditional dust removal methods have low capture efficiency for fine particles below 1 micron. Previous research on acoustic agglomeration has focused on broad-spectrum smoke, and there is a lack of understanding of the agglomeration process of sub-micron narrow-spectrum case. Based on the zoning method, the time evolution data of particle size distribution (PSD) and agglomeration efficiency corresponding to different frequencies, sound pressure levels (SPLs), and particle concentrations under the sub-micron narrow-spectrum condition are calculated in this paper. The data analysis shows that the agglomeration efficiency of the fine particle dominated flue gas increases with the increase in the frequency of action. High sound intensity conditions are conducive to improving the agglomeration efficiency, and high flue gas concentration conditions can significantly reduce the emission reduction time and energy consumption. Compared with broad-spectrum flue gas, due to the small difference in particle size and movement speed, under the same action conditions, fine particles occupy a longer agglomeration time, and the required acoustic intensity is higher, which is not conducive to practical industrial applications. Therefore, after adding a small amount of large-size particles, the acoustic agglomeration of fine particles dominated smoke was studied. Theoretical analysis shows that the presence of a small number of large particles in the flue gas significantly enhances the agglomeration efficiency and reduces the time of action and the acoustic intensity. In-plant tests verified the feasibility of acoustic agglomeration in the real-time treatment of sintered flue gas and the advantage of adding a small amount of large particles. The test sound frequency range is 50 Hz to 2 kHz, the fundamental frequency SPL is 87.3 ~ 161.8dB, and the action time is within 3s. The measured PM2.5 emission reduction efficiency is 16% ~ 92%, and the optimal frequency is about 800Hz.